Case report of a Gore-Tex TCPC conduit dissection causing severe stenosis. Issue 11 (26th October 2021) - Bates, Oliver; Semple, Thomas; Krupickova, Sylvia; Bautista-Rodriguez, Carles
Abstract: Background: The patient is a 15-year-old male with situs inversus, dextrocardia, bilateral superior caval veins, atrioventricular discordance with a single outlet, large perimembranous ventricular septal defect, aortic override, pulmonary atresia, and right aortic arch. The complex anatomy with a Ventricular Septal Defect (VSD) distant from the aorta (unsuitable for baffling to the aorta) meant he was unsuitable for biventricular repair and proceeded down a univentricular palliation pathway. Case summary: Post-total cavopulmonary connection his clinical course was uneventful until the age of 5 when he developed fatigability with desaturation. An accessory hepatic vein was surgically banded with improved saturations and exercise tolerance. At the age of 15, cardiovascular magnetic resonance (CMR) was performed to investigate borderline saturations and as workup for transition to adult services. Cardiovascular magnetic resonance and cardiac computed tomography (CT) imaging demonstrated an eccentric thrombus causing stenosis of the extracardiac conduit and a thrombus outside of the lumen contained by the thin outer membrane of the Gore-Tex conduit. Collateralization suggested this was longstanding. Cardiac catheterization demonstrated a 4 mm × 6 mm stenosis at the junction of the conduit with the pulmonary arteries. The region was successfully balloon dilated and stented with a 34 mm-long Cheatham Platinum stent, with no complications. Discussion: To date, this is the first documented case of a dissecting thrombus of a Gore-Tex graft in the literature. This case emphasizes the need for anticoagulation and serial cross-sectional imaging (CT or CMR) in Fontan patients with prosthetic grafts throughout a patients' lifetime.